Artificial neural network and SARIMA based models for power load forecasting in Turkish electricity market - Bozkurt, Omer Ozgur; Biricik, Goksel; Taysi, Ziya Cihan (PUBLIC LIBRARY SCIENCE, 2017)
Load information plays an important role in deregulated electricity markets, since it is the primary factor to make critical decisions on production planning, day-to-day operations, unit commitment and economic dispatch. Being able to predict the load for a short term, which covers one hour to a few days, equips power generation facilities and traders with an advantage. With the deregulation of electricity markets, a variety of short term load forecasting models are developed. Deregulation in Turkish Electricity Market has started in 2001 and liberalization is still in progress with rules being effective in its predefined schedule. However, there is a very limited number of studies for Turkish Market. In this study, we introduce two different models for current Turkish Market using Seasonal Autoregressive Integrated Moving Average (SARIMA) and Artificial Neural Network (ANN) and present their comparative performances. Building models that cope with the dynamic nature of deregulated market and are able to run in real-time is the main contribution of this study. We also use our ANN based model to evaluate the effect of several factors, which are claimed to have effect on electrical load.
Keywords: SHORT-TERM LOAD; TIME-SERIES; HYBRID MODEL; ALGORITHM; PRICE; Science & Technology - Other Topics